Consumer psychology of tourism, hospitality and leisure. - Crouch, Geoffrey I. (Geoffrey Ian), 1954- (CABI Pub., 2004)
This book focuses on consumer behaviour in the context of tourism, hospitality and leisure. It comprises of 8 parts that discuss: attitudes, emotions and information processing; motivation and learning; consumption systems; decision and choice; experience and satisfaction; market segmentation; attraction and loyalty; and image and interpretation. The book consists of 26 chapters and is indexed.